EU Electricity Policymakers’ (in) Sensitivity to External Factors: A Multi-decade Quantitative Analysis - Bostan, Mircea (Mike) (International Journal of Energy Economics and Policy, 2021)
The article explores a possible reason for the consistent dominance in the EU energy space of one energy policy priority, environment, when a more balanced policy would be expected, according to the classical energy trilemma. Stemming from a policy dynamics theoretical background, the sensitivity of EU policymakers to external factors is quantitatively tested by comparing legislative output against key relevant indicators, such as the public opinion and air pollutants emissions. The study encapsulates the last three decades, across all the three energy pillars of the energy trilemma, plus a fourth, internal energy market. The investigation converts into ordinal values data from selected indicators so as to create comparable scales. Results show that, unlike other energy pillars, which display strong connections between external factors and legislative output, environment legislation is rather indifferent to external factors pressure. Possible explanations are incorrect policy calibration or internal factors, originating in the rational choice realm. This research is one of the first to introduce comparative assessments in the Environmental Policy Integration discussion and employs in novel ways research methods for energy policy analysis emerged in the field of energy security policies. Keywords: electricity policy; policy dynamics; quantitative analysis; classical energy trilemma JEL Classifications: F530; Q480 DOI: https://doi.org/10.32479/ijeep.11630